Cutaneous Adverse Events in the Randomized, Double-Blind, Active-Comparator DECIDE Study of Daclizumab High-Yield Process Versus Intramuscular Interferon Beta-1a in Relapsing-Remitting Multiple Sclerosis. Issue 7 (July 2016) - Krueger, James; Kircik, Leon; Hougeir, Firas; Friedman, Adam; You, Xiaojun; Lucas, Nisha; Greenberg, Steven; Sweetser, Marianne; Castro-Borrero, Wanda; McCroskery, Peter; Elkins, Jacob
Abstract Introduction Cutaneous adverse events (AEs) have been observed in clinical studies of daclizumab high-yield process (HYP) in relapsing-remitting multiple sclerosis (RRMS). Here, we report cutaneous AEs observed in the randomized, double-blind, active-comparator DECIDE study (ClinicalTrials.gov identifier, NCT01064401). Methods DECIDE was a randomized, double-blind, active-controlled phase 3 study of daclizumab HYP 150 mg subcutaneous every 4 weeks versus interferon (IFN) beta-1a 30 mcg intramuscular (IM) once weekly in RRMS. Treatment-emergent AEs were classified and recorded by investigators. Investigators also assessed the severity of each AE, and whether it met the criteria for a serious AE. Cutaneous AEs were defined as AEs coded to the Medical Dictionary for Regulatory Activities System Organ Class of skin and subcutaneous tissue disorders. The incidence, severity, onset, resolution, and management of AEs were analyzed by treatment group. Results Cutaneous AEs were reported in 37% of daclizumab HYP-treated patients and 19% of IFN beta-1a-treated patients. The most common investigator-reported cutaneous AEs with daclizumab HYP were rash (7%) and eczema (4%). Most patients with cutaneous AEs remained on treatment (daclizumab HYP, 81%; IM IFN beta-1a, 90%) and had events that were mild or moderate (94% and 98%) and subsequently resolved (78% and 82%). Most patients with cutaneous AEs did not require treatment with corticosteroids or were treated with topical corticosteroids (daclizumab HYP, 73%; IM IFN beta-1a, 81%). Serious cutaneous AEs were reported in 14 (2%) daclizumab HYP patients and one (<1%) IM IFN beta-1a patient. Conclusion There was an increased risk of cutaneous AEs with daclizumab HYP. While physicians should be aware of the potential for serious cutaneous AEs, the typical cutaneous AEs were mild-to-moderate in severity, manageable, and resolved over time. Funding Biogen and AbbVie Biotherapeutics Inc. Trial registration ClinicalTrials.gov identifier, NCT01064401.